Increased rhinovirus replication in nasal mucosa cells in allergic subjects is associated with increased ICAM‐1 levels and endosomal acidification and is inhibited by L‐carbocisteine - Yamaya, Mutsuo (Immun Inflamm Dis, 2016)
Increased viral replication and cytokine production may be associated with the pathogenesis of asthma attacks in rhinovirus (RV) infections. However, the association between increased RV replication and enhanced expression of intercellular adhesion molecule‐1 (ICAM‐1), a receptor for a major RV group, in airway epithelial cells has remained unclear. Furthermore, the inhibitory effects of mucolytics, which have clinical benefits in asthmatic subjects, are uncertain. Human nasal epithelial (HNE) cells were infected with type 14 rhinovirus (RV14), a major RV group. RV14 titers and cytokine concentrations, including interleukin (IL)‐6 and IL‐8, in supernatants, RV14 RNA replication and susceptibility to RV14 infection were higher in HNE cells obtained from subjects in the allergic group (allergic subjects) than in those from subjects in the non‐allergic group (non‐allergic subjects). ICAM‐1 expression and the number and fluorescence intensity of acidic endosomes from which RV14 RNA enters the cytoplasm were higher in HNE cells from allergic subjects, though substantial amounts of interferon (IFN)‐γ and IFN‐λ were not detected in the supernatant. The abundance of p50 and p65 subunits of transcription factor nuclear factor kappa B (NF‐κB) in nuclear extracts of the cells from allergic subjects was higher compared to non‐allergic subjects, and an inhibitor of NF‐κB, caffeic acid phenethyl ester, reduced the fluorescence intensity of acidic endosomes as well as RV titers and RNA. Furthermore, a mucolytic agent, L‐carbocisteine, reduced RV14 titers and RNA levels, cytokine release, ICAM‐1 expression, the fluorescence intensity of acidic endosomes, and NF‐κB activation. The increased RV14 replication observed in HNE cells from allergic subjects might be partly associated with enhanced ICAM‐1 expression and decreased endosomal pH through NF‐κB activation. L‐Carbocisteine inhibits RV14 infection by reducing ICAM‐1 and acidic endosomes and may, therefore, modulate airway inflammation caused by RV infection in allergic subjects.